Pengaruh skeptisme profesional dan kompetensi auditor terhadap kualitas audit jarak jauh pada masa pandemi Covid-19 pada kantor Akuntan Publik di Bandung - Suci Fitria Cisadani; Aida Wijaya (Owner : Riset dan Jurnal Akuntansi, 2022)
Audit quality is the market value probability that the audit report will find opportunities in the financial statements, namely violations of the client's accounting system. In order to support audit quality, auditors must have a skeptical and competent attitude. The formulation of the problems studied in this study are: (1) How is the effect of professional skepticism of auditors on remote audit quality during the Covid-19 pandemic. (2) How does auditor competence affect remote audit quality during the Covid-19 pandemic. (3) How does professional skepticism and auditor competence affect remote audit quality during the Covid-19 pandemic. This study aims to determine the effect of professional skepticism and auditor competence on remote audit quality during the Covid-19 pandemic. The sample method used is simple random sampling method with a sample of 50 auditors at the Bandung City Public Accountant Office. The data analysis method used in this research is using multiple linear regression analysis method using SPSS 25 software. The results of this study indicate that professional skepticism (X1) and Auditor competence (X2) has a positive and significant effect simultaneously on quality of remote audits during the covid-19 pandemic (Y).